Investigating the Relationship between Manager and Shareholder Using game theory: Applying Accounting Conservatism and Financial Reporting Quality - SAFFAR, YOUSEF; NODEH, FAZEL MOHAMMADI; REZAEI, FARZIN; SADRARA, MEHRDAD (The journal of contemporary issues in business and government, 2021)
The decision-making of managers in today's organizations is crucial due to increased complexity of internal and external influential factors and increased competition among organizations. Game theory attempts to model the mathematical behavior of a strategic situation. This situation arises when the success of one side of the game depends on the strategies selected by other side. The present study aims at finding a strategy to maximize the balance interests of managers and shareholders by applying strategic characteristics of accounting information and accounting conservatism. The statistical population of study included 132 companies listed on the Tehran Stock Exchange during a period of seven years (2012-2018). The data analysis method is inferential and SPSS software was used to prepare the data and estimate the models. Pooled data model was used to test the research hypotheses. The results of testing the research hypotheses show that the combination of strategies of manager low reporting quality-shareholder low reporting quality (m1, S1), manager high reporting quality- shareholder high reporting quality (m2, S2), manager low conservatism - shareholder low conservatism (m3, S3), manager high conservatism - shareholder high conservatism (m4, s4), were selected as poor Nash equilibrium. The study results show that game theory plays a major role in the relationship between managers and shareholders and finding equilibrium points of game can play an effective role in the decisions of game parties (managers and shareholders). Accordingly, it informs the parties of game of the strategy that has highest utility for them.